Motif Pengguna Aplikasi Tempo Di Kalangan Ibu Rumah Tangga - Atina Ramayanti Ramayanti; Sri Narti; Yanto Yanto (Jurnal Multidisiplin Dehasen (MUDE), 2023)
The purpose of this research is to find out the users’ motive in using Tempo application among housewives. This research is descriptive qualitative research, data are collected by using observation, interview and documentation. In selecting the informant, the researcher uses purposive sample technique means that people who become informants are Tempo application users with criteria decided by researcher. There are 5 housewives as informants at Pasar tais of Seluma Regency. the focus which conducted by researcher is to find out the motive used by users by using Rachmat motive theory. The theory consists of cognitive and affective motives. According to the result of research, cognitive motive of the users in using the application is to obtain the information about how to do wedding make-up, dressed with other culture and knowledge about the lates artists’ make up, also the information about model dressing and wedding dress. In affective motive, the happy feeling because the users can feel the latest wedding model, obtain new experiences and expect for praise and happy if the content is viral and expect to get positive feedback from people.